GAMBARAN GAYA HIDUP LANSIA PENDERITA OSTEOARTHRITIS - Yulianti, Rima (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
The spread of osteoarthritis is more common in the elderly, one caused by lifestyle. This study aims to identify the lifestyle picture of elderly osteoarthritis sufferers in the elderly at the Rejosari Health Center. Methods: This study uses a descriptive research design. The sample in this study were 75 respondents using a purposive sampling technique. The measuring tool used is a lifestyle questionnaire that has been tested for validity and reliability and obtained a Crombach Alpha value of 0.925 >0.6 which was widely disseminated. Results: The study showed that the majority of osteoarthritis respondents are aged 60-69 years (73.3%), female (56.0%), elementary school education level (32.0%), housewife (44.0%), and ethnic Malay (40.0%). The results of the lifestyle of the respondents were physical activity in the inactive category 42 respondents (56.0%), the category of bad eating patterns 48 respondents (64.0%) and the category of smoking habits 46 respondents (61.3%) high exposure to cigarette smoke. Conclusion: The results of this study indicate that some of the elderly are not active in their physical activities, have a poor diet and are passive smokers. Suggestion: Elderly people with osteoarthritis to pay attention to their lifestyle, especially in physical activities in order to prevent and reduce the impact of osteoarthritis suffered.